Analisis Pengendalian Internal Dan Insentif Terhadap Produktivitas Kerja Dengan Disiplin Kerja Sebagai Variabel Intervening (Studi Pada Titik Terang Konveksi) - Ngamal, Ignasius Rezaldi; Kirana, Kusuma Candra; Kurniawan, Soni (Universitas Muhammadiyah Metro, 2023)
This study was conducted to analyze the effect of Internal Control and Incentives on Work Productivity with Work Discipline as an Intervening Variable (Study on Titik Terang Konveksi). The population in this study amounted to 48 employees. The sample of this study used the saturated sample technique, so the research sample was set at 48 employees. This study uses a quantitative approach, the data for this study obtained through research questionnaires that have been filled out by respondents who have been determined. The data analysis method used is the multiple linear regression analysis method with the help of SPSS version 23.0. The results of this study indicate that there is a significant effect of internal control on work discipline, there is an insignificant effect of incentives on work discipline, there is a significant effect of incentives on work productivity. And with the results of the Sobel test it was found that there was a significant effect of internal control on work productivity mediated by work discipline, there was an insignificant effect of incentives on work productivity mediated by work discipline on employees of Titik Terang Konveksi.Keywords: Internal Control, Incentives, Work Discipline, Work Productivity.